1999
DOI: 10.1292/jvms.61.803
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Analysis of the Endocrine and Exocrine Pancreas in Twelve Cattle with Insulin-Dependent Diabetes Mellitus (IDDM)

Abstract: Histological and immunohistochemical studies were carried out on the pancreas of twelve cattle of insulin-dependent diabetes mellitus (IDDM). They showed clinical signs such as persistent hyperglycemia, glycosuria and decreased glucose tolerance, and some cases accompanied with or without ketonuria. Histopathologically, eight cattle were diagnosed as chronic IDDM, while others were acute IDDM. The most characteristic lesions of the pancreas in chronic IDDM showed a decrease in the size and number of pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Clinical investigations and experimental laboratory research supported by morphological and ultrastructural observations indicate a close relation between pancreatic exo-and endocrine parts (Okabayashi et al, 1988;Aughsteen and Kataoka, 1993;Meral et al, 2001) Insulin and glucagon actions have been investigated in great detail and clinical studies in diabetic patients show that the impairment of pancreatic exocrine functions is due to insulin deficiency and relative glucagon predominance (Adeghate, 1999;Taniyama et al, 1999;Hardt et al, 2000;Lernmark, 2000;Harding et al, 2001). Reports regarding the influence of insulin deficiency on the pancreatic exocrine function describe distinctive changes in composition and quality of pancreatic juice as well as its decreased production (Okabayashi et al, 1988;Aughsteen and Kataoka, 1993;Kim et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical investigations and experimental laboratory research supported by morphological and ultrastructural observations indicate a close relation between pancreatic exo-and endocrine parts (Okabayashi et al, 1988;Aughsteen and Kataoka, 1993;Meral et al, 2001) Insulin and glucagon actions have been investigated in great detail and clinical studies in diabetic patients show that the impairment of pancreatic exocrine functions is due to insulin deficiency and relative glucagon predominance (Adeghate, 1999;Taniyama et al, 1999;Hardt et al, 2000;Lernmark, 2000;Harding et al, 2001). Reports regarding the influence of insulin deficiency on the pancreatic exocrine function describe distinctive changes in composition and quality of pancreatic juice as well as its decreased production (Okabayashi et al, 1988;Aughsteen and Kataoka, 1993;Kim et al, 2000).…”
mentioning
confidence: 99%
“…Interestingly, the relation between insulin and glucagon concentrations in extracellular fluid and their antagonistic actions also seem to play a key role in pancreatic exocrine function disorders. Insulin is recognised as the main factor stimulating exocrine activity, whilst glucagon is ascribed an inhibitory role, not only in the processes of synthesis but also in the secretion of amylase and HCO 3 -ions (Taniyama et al, 1999;Hardt et al, 2000), as shown in both functional tests as decreased enzyme activity and ionic shi�s, and in histopathological observations in the form of involutional changes, exocrine cell degranulation and texture atrophy (Minami et al, 1999;Harding et al, 2001). Amylase -one of the main enzymes produced in exocrine pancreatic cells, may be recognised as an adequate indicator of organ's activity both in physiological and pathological states.…”
mentioning
confidence: 99%
“…The major type of diabetes mellitus observed in dogs and cats is insulin-dependent at the time of diagnosis (Feldman and Nelson, 2004;Rand and Marshall, 2005), and in cattle, insulinopenic diabetes is known to develop after infection with bovine viral diarrhea virus (Taniyama et al, 1999). Thus, the fact cannot be excluded that these results could also be beneficial in clinical veterinary settings.…”
Section: Discussionmentioning
confidence: 99%
“…
[23][24][25][26]. Young individuals are constantly affected, the age ranging between 6 months and 5 years of age.
…”
mentioning
confidence: 99%
“…The results of these tests proved that the glucose disappearance rate and half time were longer than in normal control cows. Elevated values of serum fructosamine were also observed [22,25]. …”
mentioning
confidence: 99%